2021
DOI: 10.3389/fnins.2021.641951
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Target and Multi-Session Transcranial Direct Current Stimulation in Patients With Prolonged Disorders of Consciousness: A Controlled Study

Abstract: Objectives: To investigate the effect of multi-session transcranial direct current stimulation (tDCS) over the prefrontal area, left dorsolateral prefrontal cortex (DLPFC), and bilateral fronto-temporo-parietal cortices (FTPCs) in patients with prolonged disorders of consciousness (DOC) and to examine the altered cortical interconnections using non-linear electroencephalography (EEG).Methods: In this open-label controlled study, conventional treatments were implemented in both the control and tDCS groups, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Another study by our group assessing psychomotor inhibition state (PIS) after TBI in cases who recovered from UWS showed that multi-target (prefrontal area, left DLPFC) anodal tDCS could improve PIS . Furthermore, our most recent study confirmed that multitarget tDCS [prefrontal area, left DLPFC and bilateral frontotemporo-parietal cortices (FTPCs)] could overall improve the prognosis of DOC patients and the prognosis of patients in tDCS group (12/29, UWS to MCS) was significantly better than that in the control group (4/28, UWS to MCS) (Zhang et al, 2021). The above results suggest that multi-target tDCS combined with EEG (tDCS-EEG) is a promising method for predicting the prognosis of UWS patients.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Another study by our group assessing psychomotor inhibition state (PIS) after TBI in cases who recovered from UWS showed that multi-target (prefrontal area, left DLPFC) anodal tDCS could improve PIS . Furthermore, our most recent study confirmed that multitarget tDCS [prefrontal area, left DLPFC and bilateral frontotemporo-parietal cortices (FTPCs)] could overall improve the prognosis of DOC patients and the prognosis of patients in tDCS group (12/29, UWS to MCS) was significantly better than that in the control group (4/28, UWS to MCS) (Zhang et al, 2021). The above results suggest that multi-target tDCS combined with EEG (tDCS-EEG) is a promising method for predicting the prognosis of UWS patients.…”
Section: Introductionmentioning
confidence: 60%
“…Many studies and our previous studies have found that prefrontal-parietal cortical networks plays a critical role in improvement in patients with UWS (Cavinato et al, 2015(Cavinato et al, , 2019Naro et al, 2016a,b;Bai et al, 2017a,c;Cacciola et al, 2019;Zhang et al, 2021). The application of active tDCS on OFC can improve the level of consciousness by improving the residual connectivity between prefrontal lobe and motor area (Naro et al, 2015).…”
Section: Reasons For Designing a Historical Controlled Trialmentioning
confidence: 88%
See 1 more Smart Citation
“…A higher C-ApEn value indicated more cortical interconnections ( 41 ). The expression formula and parameters had been described in our previous studies ( 33 , 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among possible non-linear dynamics measures, cross approximate entropy (C-ApEn) was used to analyze two related time series and measure their degree of asynchrony by comparing sequences from one series to those of the second series to reflect the spatial decorrelation of cortical potentials from two remote sites ( 32 ). Our previous study showed that the EEG non-linear index of C-ApEn revealed altered cortical interconnections after tDCS treatment in patients with prolonged disorders of consciousness ( 33 ). As the EEG examination is easy to operate and the word repetition tasks during EEG can be completed within a short time, EEG is a suitable tool for dynamically observing network activity in research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%